CURRENT APPROACHES TO EVALUATION OF THE MULTIVESSEL CORONARY ATHEROSCLEROSIS IN PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE - D. N. Perutsky; I. B. Kovalenko; S. L. Konstantinov; T. I. Makeeva; M. V. Filatov (Столичная издательская компания, 2016)
Aim. To determine the validity of stress echocardiography by fractional reserve blood flow (FFR) as the reference method in detection of coronary arteries requiring revascularization, as well as to optimize the determination of the functional significance of coronary artery lesions in patients with multivessel coronary atherosclerosis. Material and methods. Patients (n=36) with stable angina class 2-3 with multivessel coronary atherosclerosis were included into the study. Stress echocardiography with dobutamine or exercise test (treadmill) was performed in all patients. Selective coronary angiography with subsequent evaluation of FFR was carried out in patients with a positive result of stress echocardiography. Totally 108 arteries (87 with stenosing atherosclerosis) were assessed.  Results. According to coronary angiography bi-vessel and three-vessel damages were revealed in 21 (58%) and 15 (42%) patients, respectively. Method of stress echocardiography as compared with FFR shown sensitivity - 58%, specificity - 95%, positive predictive value - 87%, positive predictive value of a negative result - 17%. Method of coronary angiography (as a method to detect significant stenosis by visual assessment of coronary artery) as compared with FFR demonstrated sensitivity 100%, specificity - 30%, positive predictive value - 42%. Conclusion. Stress echocardiography for noninvasive patient examination improves the accuracy of determination for the need and extent of revascularization.